Strategies for Treating Alzheimer’s: Current Approaches and Future Perspectives - Skuba, Adriana; Załuska, Katarzyna; Świdniak, Agnieszka; Biskup, Marta; Bartoszek, Aleksandra; Kopeć, Karolina; Marut, Agnieszka; Misiuk, Jagoda; Adamiuk, Julia; Nykiel, Sylwia (Quality in Sport, 2025)
Introduction and Purpose: Alzheimer’s disease is the most common cause of dementia, affecting millions of people worldwide and posing a significant challenge to modern medicine. This review explores the available treatment options, their limitations, and the future directions of research that may bring breakthroughs in combating this devastating condition. Materials and Methods: This article is a comprehensive review based on a detailed analysis of peer-reviewed studies obtained from major scientific databases, such as PubMed. The selected articles focus on modern methods of treating Alzheimer’s disease, chosen for their relevance and importance to the subject. Results: This review highlights the complex pathogenesis of Alzheimer’s disease (AD), driven by amyloid-β accumulation, tau protein abnormalities, cholinergic deficits, and neuroinflammation. Current treatments, such as cholinesterase inhibitors and NMDA receptor antagonists, provide only temporary symptom relief, while emerging therapies, including immunotherapy and gene therapy, offer promising new directions. Advances in disease-modifying approaches targeting Aβ, tau, and genetic factors have shown potential, though challenges remain in achieving long-term efficacy and accessibility. Conclusion: Despite significant progress in understanding AD and developing new treatment strategies, an effective cure remains elusive. Immunotherapies and gene therapy represent promising avenues for disease modification, but further research is needed to optimize their effectiveness and accessibility. A multidisciplinary approach combining pharmacological, genetic, and lifestyle interventions is essential to improving patient outcomes and combating this devastating disease.